Clinical trials on soft tissue Sacoma, Dana-Farber Cancer Institute. - Nwangwu, John (1999)
Keywords: dept.pch; faculty_collection

Hearts' N Parks. - O'Sullivan, Ellen (Spring;Public Health., 1999)
Keywords: dept.pch; faculty_collection; sabbatical_report

Medical Ethics. - Stambler, Moses (., 1995)
Keywords: dept.pch; faculty_collection; sabbatical_report

The Study of Women's Health Issues from Expert-Based Needs and Women-Based Wants Perspectives. - Stohler, William L. (1993)
Keywords: dept.pch; faculty_collection; sabbatical_report

Interactive Video Programs for Driver Training. - Mottola, Fred (1989)
Keywords: dept.pch; faculty_collection; sabbatical_report

EMS Trauma Program, Hartford Hospital. - Gonsalves, Danny (1988)
Keywords: dept.pch; faculty_collection; sabbatical_report

Experience Marketing: Strategies for the New Millenium - O'Sullivan, Ellen Lupia; Spangler, Kathy J. (Venture Pub., 1998)
Keywords: Marketing; Marketing; Leisure; Marketing; Recreation; Parks; dept.pch; faculty_collection

Marketing for Parks, Recreation, and Leisure - O'Sullivan, Ellen Lupia (Venture Pub., 1991)
Keywords: Marketing; Marketing; Leisure; Marketing; Recreation; Parks; dept.pch; faculty_collection

A Systems Approach to Social Foundations of American Education - Stambler, Moses C. (MSS Educational Pub. Co., 1969)
Keywords: Educational sociology; dept.pch; faculty_collection

Correlates of sexual satisfaction in marriage - Young, M; Denny, George; Luquis, Raffy; Young, Tamera (Canadian Journal of Human Sexuality, 1998)
Hypotheses concerning possible correlates of sexual satisfaction in marriage were tested using the replies of 797 married women and men of diverse ages to a 70-item mailed questionnaire that contained seven Likert-type sub-scales measuring different sexual and non-sexual variables. Multiple regression analysis, using sexual satisfaction as the dependent variable, yielded a five-variable model that accounted for a significant portion of the variation in sexual satisfaction (Adjusted R Squared = .602). The variable 'overall satisfaction with marriage' had the highest correlation with sexual satisfaction (r = .622), followed by 'satisfaction with non-sexual aspects of the relationship' (r = .609), frequency of spouse/partner orgasm per sexual encounter (r = .529), frequency of sexual activity (r = .370), and 'sexual uninhibitedness' (r = .230). None of three measures of religiosity made a significant contribution to explaining the variation on self reported sexual satisfaction. Men and women did not differ in level of sexual satisfaction, and adding gender to the regression model did not increase the level of explained variation. The results indicate that sexual satisfaction in these married respondents could not be compartmentalized to their sexual interactions, but was strongly associated with non-sexual aspects of the overall marital relationship as well.
Citation Key Alias: lens.org/095-547-782-487-373 tex.type: [object Object]
Keywords: Marital satisfaction; Relationship satisfaction; Religiosity; Sexual satisfaction; Spouse-partner orgasm consistency; aged; article; dept.pch; female; human; male; marriage; multiple regression; normal human; orgasm; questionnaire; religion; satisfaction; sexual behavior; ⛔ No DOI found

Recruitment of minority students to U.S. epidemiology degree programs - George, Diane Marie M.St.; Schoenbach, Victor J.; Reynolds, Gladys H.; Nwangwu, John; Adams-Campbell, Lucile L. (Annals of Epidemiology, 1997)
PURPOSE: African-, Hispanic-, and Native Americans are underrepresented in the field of epidemiology including degree programs. As part of the assessment component of its mandate, the American College of Epidemiology Committee on Minority Affairs conducted a survey of minority recruitment activities of U.S. epidemiology degree programs. METHODS: The survey, containing questions related to marketing activities, institutional infrastructure, financial support, academic offerings, and receptive/supportive environment, was mailed to all programs identified in Episource as offering epidemiology degrees. Separate responses were requested concerning activities at the department and school levels. RESULTS: Fifty- two completed questionnaires were received (response rate of 79%). All but two institutions had at least one activity conducted by either the department or the school. However, all activities were more common at the school- than at the department-level. Indeed, some activities [a written minority student recruitment plan (6% of departments and 52% of schools), personnel with minority recruitment responsibilities (4% of departments and 73% of schools] were almost exclusively school-sponsored. Although marketing-type activities were the most common minority recruitment tool used by departments, only 21% made visits to minority schools, 17% visited other colleges specifically to recruit minorities, and 12% produced materials targeted to ethnic/racial minorities. Six percent of the departments and 19% of the schools offered financial support (grants, fellowships, scholarships) to almost all underrepresented minority students. CONCLUSIONS: Even though individual epidemiology degree programs may not see a need for general recruitment activities in order to maintain the size of their applicant pool, minority- specific recruitment activities should be undertaken to enhance and diversify that pool. We recommend that epidemiology departments develop, adopt, and implement comprehensive written plans for the recruitment of underrepresented minority students into their programs.
6 citations (Crossref) [2023-10-31] Citation Key Alias: pop00101 tex.type: [object Object]
Keywords: Adult; Career Choice; Educational Measurement; Epidemiology; Fellowships and Scholarships; Female; Humans; Male; Minority Groups; Minority groups; Minority health; School Admission Criteria; Schools; Public Health; Schools- veterinary; Schools-public health; Student recruitment; United States; article; dept.pch; education program; epidemiology; human; minority group; priority journal; questionnaire; student; united states

The impact of the Yale faculty development program: Clinical alcohol and drug research and education (cadre) on medical student teaching about substance abuse - O'Connor, Patrick G.; Pearsall, H. Rowland; Ball, Samuel A.; Forsyth, Brian W. C.; Faraclas, William G.; Schottenfeld, Richard S. (Substance Abuse, 1997)
Increasing emphasis on the need for medical student education about substance abuse has led to the development of a variety of training efforts through faculty development. The Yale University School of Medicine Faculty Development Program or CADRE (Clinical Alcohol and Drug Research and Education) was instituted in 1992 for the purpose of enhancing substance abuse teaching in the Yale medical student curriculum. CADRE faculty were identify in internal medicine, pediatrics, and psychiatry. Prior to the program, there was limited formal teaching about substance abuse in the Yale curriculum and no coordinated effort across disciplines. The enhancement of teaching activities occurred primarily within four required “core”; clinical clerkships for third‐and fourth‐year medical students. Student evaluations of this new teaching activity were positive. The CADRE program was successful at developing a multidisciplinary core faculty group with expertise in substance abuse teaching and resulted in the development of a coordinated, multidisciplinary substance abuse curriculum for Yale medical students.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/156-310-363-042-797, pop00179 tex.type: [object Object]
Keywords: Faculty development; Medical education; Substance abuse; article; clinical research; curriculum; dept.pch; education program; faculty development; medical education; medical student; substance abuse; teaching

New admission measure needed - Williams, AL; Gallup, P (Academic Medicine, 1997)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1997WN84700001
Keywords: Humans; School Admission Criteria; Schools; Medical; United States; dept.pch; education; human; letter; medical school

Homeless mentally ill veterans: race, service use, and treatment outcomes. - Rosenheck, Robert A; Leda, Catherine; Frisman, Linda K; Gallup, Peggy (American Journal of Orthopsychiatry, 1997)
Comparisons of service use and treatment outcomes for 145 black and 236 white homeless veterans with mental disorders showed few differences. A greater improvement in psychiatric symptoms and alcohol problems among white than black veterans did not hold true when black veterans had participated in the residential treatment component of the program. The implications of the findings for the successful treatment of homeless black veterans are discussed.
16 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/043-248-001-349-482 tex.type: [object Object]
Keywords: Adult; African Americans; European Continental Ancestry Group; Female; Hispanic Americans; Homeless Persons; Humans; Male; Mental Disorders; Mental Health Services; Middle Aged; Residential Treatment; Veterans; article; cost effectiveness analysis; dept.pch; homelessness; mental disease; mental health service; outcomes research; race difference; residential care; soldier; treatment outcome

Measurement of the proportion of free to total prostate-specific antigen improves diagnostic performance of prostate-specific antigen in the diagnostic gray zone of total prostate-specific antigen - Luderer, Albert A.; Chen, Ya-Ting; Soriano, Thomas F.; Kramp, William J.; Carlson, Grant D.; Cuny, Carol; Sharp, Thomas; Smith, William; Petteway, Jason; Brawer, Michael K.; Thiel, Robert (Urology, 1995)
Objectives: This study examined the clinical significance of non-complexed (free) prostate-specific antigen (PSA) in the differential diagnosis of prostate cancer with an emphasis on patients with total PSA values between 4.0 and 10.0 ng/mL (the diagnostic gray zone). Methods: Serum samples were obtained from three specimen banks. Patient samples consisted of 55 untreated historically confirmed primary cancer, 62 men with untreated benign prostatic disease histologically confirmed by 6 negative sextant biopsies, and 64 asymptomatic healthy male controls with normal digital rectal examinations and PSA values less than 4.0 ng/mL. All patients were between the ages of 50 and 75 years. Total PSA levels were determined using the PA immunoassay performed on the TOSOH AIA-1200 automated immunoassay instrument. Free PSA levels were determined using a monoclonal-polyclonal antibody sandwich radioimmunoassay. The proportion of free to total PSA was calculated by dividing the patient's free PSA value by the total PSA value. Results: When all subjects were included, both total PSA and the proportion of free to total PSA significantly differentiated between patients with prostate cancer and patients with benign histologic conditions (P< 0.0001). However, in men with total PSA values between 4.0 and 10.0 ng/mL, the proportion of free to total PSA significantly differentiated between patients with benign and malignant histologic conditions (P = 0.0004), whereas the total PSA did not (P = 0.13). Among this subgroup of patients, the analysis of sensitivity and specificity showed that the proportion of free to total PSA had a clearly higher specificity compared with that of the total PSA at the same level of sensitivity. Conclusions: Measurement of the free PSA level in a patient's serum and calculation of the proportion of free to total PSA enhances the ability to distinguish benign histologic conditions from cancer while retaining high sensitivity for detecting cancer in men who present with total PSA levels between 4.0 and 10.0 ng/mL. A large-scale population-based study is currently in progress to confirm this preliminary finding. © 1995.
207 citations (Crossref) [2023-10-31] Citation Key Alias: pop00002 tex.type: [object Object]
Keywords: Aged; Case-Control Studies; Chromatography; High Pressure Liquid; Comparative Study; Diagnosis; Differential; Human; Immunoassay; Male; Middle Age; Prostate-Specific Antigen; Prostatic Hyperplasia; Prostatic Neoplasms; ROC Curve; Radioimmunoassay; Reference Values; Sensitivity and Specificity; adult; article; cancer diagnosis; controlled study; dept.pch; diagnostic accuracy; differential diagnosis; early diagnosis; human; immunoassay; major clinical study; male; monoclonal antibody; polyclonal antibody; priority journal; prostate cancer; prostate specific antigen; tumor marker